LEADERSHIP THAT BRINGS CHANGE IN SCHOOLS IN ACHIEVING SUCCESS - Sumarto Sumarto (International Journal of Southeast Asia, 2020)
A transformational leader explains how leaders transform organizations by creating, communicating and inspiring. To shift a change in instilling a culture of madrasah with good teaching and learning process, fulfillment and repair facilities, academic achievement and extracurricular, religious worship, discipline and cooperation of both internal and external. The purpose of this study was to find out why the headmaster who can instill cultural transformational madrasas, the role of transformational leadership and the success of transformational leadership role in instilling a culture of madrassas in the province of Jambi. The approach used in this study is a qualitative descriptive approach. Data collection techniques using observation, interviews and documentation. Analysis of the data using the model of Miles and Huberman and data validity technique uses triangulation data. The results of the study, namely: Principals have Muslim personality as Prophet, know the needs of members, build confidence and members, building a shared commitment to make the shift towards change for the better, creative, productive and innovative, exemplary and courage to face challenges, sensitivity to complaints and suggestions of members, deliberation and spirit of motivation. The role of transformational leadership Principals for direction (Direction Setter), change agents (Agents of Change), interpreter Talk (Spokesperson), coach (Coach) is good, fund support (support-getter), the guarantor of success (success-guarantor) and a guide to make the shift change labih good (path-finder). The practical implications, namely: The role of transformational leadership Principals in instilling a culture of madrasah is to apply Idealiced influence, Inspirational motivation, Intelelectual stimulation and Individualized consideration and achieving success with the personality of a good leader, also by a factor of education, experience high and good cooperation.